Development of multiplex real-time PCR for the rapid detection of five bacterial causes of community acquired pneumonia - Mahmud, Mohammed Imad A.; Al-Marzooq, Farah; How, Soon Hin (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Establishing a microbial diagnosis for patients with community-acquired pneumonia (CAP) is still challenging and is often achieved in only 30-50% of cases. Polymerase chain reaction (PCR) has been shown to be more sensitive than conventional microbiological methods and it could help to increase the microbial yield for CAP patients. This study was designed to develop, optimize and evaluate multiplex real-time PCR as a method for rapid differential detection of five bacterial causes of CAP namely Streptococcus pneumoniae, Burkholderia pseudomallei and atypical bacterial pathogens, Mycoplasma pneumoniae, Chlamydophila pneumoniae and Legionella pneumophila. Duplex and triplex real-time PCR assays were developed using five sets of primers and probes that were designed based on an appropriate specific gene for each of the above CAP pathogens. The performance of primers for each organism was tested using SYBR Green melt curve analysis following monoplex realtime PCR amplification. Monoplex real-time PCR assays were also used to optimize each primers-probe set before combining them in multiplex assays. Two multiplex real-time PCR assays were then optimized; duplex assay for the differential detection of S. pneumoniae and B. pseudomallei, and triplex assay for the atypical bacterial pathogens. Both duplex and triplex real-time PCR assays were tested for specificity by using DNA extracted from 26 related microorganisms and sensitivity by running serial dilutions of positive control DNAs. The developed multiplex real-time PCR assays shall be used later for directly identifying CAP causative agents in clinical samples. INTRODUCTION The etiologic diagnosis of CAP remains an uneasy task, with the causative organisms often identified in only up to 50% of cases. This is mainly due to difficulties in culturing and to the delayed results associated with conventional methods (serology and culture), which often allow a retrospective diagnosis only (Chan et al., 2007; Nolte, 2008). Molecular methods such as PCR offer a better approach for the rapid diagnosis of CAP (Benson et al., 2008). Several conventional PCR assays have been developed for each individual respiratory pa